Shift or Maintenance: The Effects of Gender on Language Use among transplanted Khowar Speakers in Karachi, Pakistan - Muhammad Hassan Abbasi; Maya Khemlani David; Hera Naz (Journal of Communication and Cultural Trends, 2023)
Pakistan is a multiethnic country with different cultures and languages. There are approximately 74 languages spoken in the country (Siddiqui, 2019), year). However, different communities tend to migrate from their hometowns or rural areas to cities due to geographical, social, and economic mobility. In cities, these communities tend to adopt a new identity, culture, and language to sustain themselves. Karachi is the provincial capital and a hub of various speech communities facing various issues. The current study focused on an inter-provincial migrated Khowar community and their language usage at home, neighborhood, educational institutions, and workplace domains in Karachi. It investigated their patterns of language use with a specific focus on male and female Khowar speakers who have different roles and exposures in the society. A qualitative case study was undertaken using purposive and snowball sampling techniques. The data for linguistic choices was taken from 20 young male and female Khowar speakers enrolled in a public sector university through semi-structured interviews. The interviews were then transcribed and underwent thematic analysis. The findings revealed differences in patterns of language use across gender. Female Khowar speakers preserve their language in their homes, neighborhoods, and educational institutions. While, the male speakers shift to Urdu and English in educational and social domains. However, language practices for both male and female speakerschange within the workplace domain since Urdu is used as a common lingua franca for wider communication. Although, the patterns of language use have begun to change; still, the male and female Khowar speakers maintain a strong ethnolinguistic identity and affiliation with their community. Government, community members, and policymakers must be made aware of shifting language use among Khowar and other ethnic communities.